Potensi Geowisata Terpadu Berbasis Komunitas (Community-Based Tourism) Pada Pemandian Air Panas Jorong Gurah, Nagari Batu Bajanjang, Kabupaten Solok - Rahmat Ksatria Afrul; Muhammad Azka Nashan; Hafizhah Hidayati; Oxa Fathona Suri; Nurul Barorah Gusri; Miftahul Jannah; Muhammad Farhan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The Hot Spring Bath of Jorong Gurah, located in Nagari Batu Bajanjang, Solok Regency, West Sumatra, is a geothermal-based natural resource with great potential to be developed as an integrated community-based geotourism (Community-Based Tourism/CBT) destination. This study aims to identify and analyze the geotourism potential of the Jorong Gurah Hot Spring, examine the involvement of local communities—including the participation of KKN students from Universitas Negeri Padang—in tourism development efforts, and formulate sustainable development strategies. The research method used is descriptive qualitative research with field observation approaches, in-depth interviews with local residents, and documentation analysis. The results indicate that this location has significant geotourism potential, including natural Hot spring sources with beneficial mineral content, beautiful mountain landscapes, and the distinctive local wisdom of farming communities. As a concrete contribution, UNP KKN students installed directional signboards containing information about the bathing location, the division of male and female zones, and information that the facility is free and open to the public. The formulated CBT program includes cultural ecotourism development, agrotourism Based on local agriculture, and community economic empowerment through the tourism sector.